Hubungan Self-Efficacy Dan Kompetensi Profesional Dengan Kinerja Guru Pada Sekolah Menengah Atas Di Sub Rayon 11 Parung Kabupaten Bogor - Nur Isyanto; EE. Junaedi Sastradiharja (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2019)
This research aims to identify and test empirical data related to self-efficacy relationship and professional’s competence with teacher’s performance separately and simultaneously. Results in this research, there is a positive and significant relationship between self efficacy and professional’s competence together with teacher’s performance in sub rayon 11 parung kabupaten bogor. There is a positive and significant relationship between self efficacy and teacher’s performance with a coefficient of correlation of 0.659 point and coefficient of determination of 0.435 point which gives effect with teacher performance of 43.5% and the remaining 56.5% is determined by other factors. There is a positive and significant relationship between professional’s competence with teacher’s performance with coefficient of correlation 0.659 point and coefficient of determination of 0.435 point which gives effect with teacher performance of 43.5% and the rest is 56.5% determined by other factors. There is a positive and significant correlation between self efficacy and professional’s competence together with teacher’s performance with coefficient of correlation = 0,662 point and coefficient of determination equal to 0,438 point which give effect simultaneously with teacher’s performance equal to 43,8% and the rest is 56, 2% is determined by other factors. The results coefficient of regression that self efficacy and professional’s competence together given affected for teacher’s performance in sub rayon 11 parung kabupaten bogor.